Investigação das concepções de alguns professores de biologia, física e química sobre a aprendizagem baseada em problemas - Moreno Junior, Mauro Antônio (2012)
The Problem-Based Learning methodology is presented as a methodological proposal for teaching biology, physic and chemistry which seeks to address the knowledge in an inter-related and contextualized manner able to engage students in an active process of reflection and construction of its own knowledge that can contribute to making decision and resolution of problem. BPA represents today as a global trend in science education with extremely promising results. In this context, after the application of the methodology, the present study aimed to investigate the conceptions of some teachers of biology, physics and chemistry on the PBL. To this end, we proposed a sequence of activities ranging from the presentation of the theoretical foundations to the development of learning situations, covering all stages of teaching based on PBL.The target group was composed of 11 teachers from public schools, largely linked to the Board of Education of Franca who attended voluntarily in a university extension course offered by the department postgraduate of the University of Franca titled Learning based on problems in biology classes, chemistry and physics.